Reincarnation of Bacteriocins From the Lactobacillus Pangenomic Graveyard - Collins, Fergus W. J.; Mesa-Pereira, Beatriz; O'Connor, Paula M.; Rea, Mary C.; Hill, Colin; Ross, R. Paul (Frontiers in Microbiology, 2018)
Bacteria commonly produce narrow spectrum bacteriocins as a means of inhibiting closely related species competing for similar resources in an environment. The increasing availability of genomic data means that it is becoming easier to identify bacteriocins encoded within genomes. Often, however, the presence of bacteriocin genes in a strain does not always translate into biological antimicrobial activity. For example, when analysing the Lactobacillus pangenome we identified strains encoding ten pediocin-like bacteriocin structural genes which failed to display inhibitory activity. Nine of these bacteriocins were novel whilst one was identified as the previously characterise d bacteriocin ‘penocin A’. The composition of these bacteriocin operons varied between strains, often with key components missing which are required for bacteriocin production, such as dedicated bacteriocin transporters and accessory proteins. In an effort to functionally express these bacteriocins, the structural genes for the ten pediocin homologs were cloned alongside the dedicated pediocin PA-1 transporter in both E. coli and Lactobacillus paracasei heterologous hosts. Each bacteriocin was cloned with its native leader sequence and as a fusion protein with the pediocin PA-1 leader sequence. Several of these bacteriocins displayed a broader spectrum of inhibition than the original pediocin PA-1. We show how potentially valuable bacteriocins can easily be ‘reincarnated’ from in silico data and produced in vitro despite often lacking the necessary accompanying machinery. Moreover, the study demonstrates how genomic datasets such as the Lactobacilus pangenome harbour a potential “arsenal” of antimicrobial activity with the possibility of being activated when expressed in more genetically amenable hosts.